Inactivation of Horseradish Peroxidase Enzyme in The Removal of 4-Chlorophenol from Aqueous Solution (Chemical Engineering Research Bulletin, 2008)
Analysis of the concentration-time profiles of 4-chlorophenol in aqueous solution employing horseradish peroxidase enzyme revealed removal of chlorophenol. The reaction products were retained on the enzyme carrier matrix. In the process, however; activity of enzyme was affected by deposition of reaction products on active sites of the enzyme. Apparent Â kinetics of enzyme inactivation was investigated employing a mathematical model. Inactivation constant was determined by fitting the model to experimental substrate concentration decay curves. The model can be employed to determine appropriate strategies for practical applications of immobilized horseradish peroxidase catalyst.Chemical Engineering Research Bulletin 11 (2007) 19-30